2009
DOI: 10.1097/ncc.0b013e3181a2dbd2
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge and Practice of Breast Self-examination Among Healthcare Workers in Kayseri, Turkey

Abstract: Breast cancer is the most common cancer type and cause of death among women in many countries. Monthly breast self-examination (BSE) is an effective diagnostic method for breast cancer. This study aimed to determine the knowledge level and practice frequency of BSE among healthcare workers in Kayseri, Turkey. Data were collected via a questionnaire that was prepared based on information in the literature. The questionnaire was composed of 2 sections: sociodemographic characteristics and practice and knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
7
2
Order By: Relevance
“…The percentage was lower in Poland, in the United Arab Emirates (61.5%) [39] and much higher than in India (15.6%) [38]. Among the surveyed female health care workers, nurses among them, in Turkey 17% [34], Iran 6% [35] and 39.5% regularly practised BSE [36]. In Poland, on the recommended or chosen date, BSE was performed by 67.3% nurses with regular menstruation, and by only 30.4% post-menopausal respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage was lower in Poland, in the United Arab Emirates (61.5%) [39] and much higher than in India (15.6%) [38]. Among the surveyed female health care workers, nurses among them, in Turkey 17% [34], Iran 6% [35] and 39.5% regularly practised BSE [36]. In Poland, on the recommended or chosen date, BSE was performed by 67.3% nurses with regular menstruation, and by only 30.4% post-menopausal respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The available papers concern nurses and female health care workers in Asia, i.e. Turkey [34], Iran [35,36], Pakistan [37], India [38], and the United Arab Emirates [39]. The number of examined persons in these countries was small (from 119 to 410).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire form was derived from our own experience and other published studies dealing with the same topic. The study conducted by Güleser et al [ 11 ] was particularly taken into consideration in the preparation of the items. While the first part of the questionnaire contained sociodemographic characteristics of respondents (including age, current marital status, level of education, family history of BC, and history of breast health problems), the second part consisted of items focusing on the respondents' attitudes towards BSE and their practices of BSE as well as frequency of these practices.…”
Section: Methodsmentioning
confidence: 99%
“…There are limited studies on the beliefs and behaviors of FHPs with regard to BC screening in Turkey (9)(10)(11)(12)15) and in the world (13,14). In addition to these, the results of several studies carried out in Turkey showed that FHPs may have a low sensitivity with regard to screening behavior.…”
mentioning
confidence: 97%
“…In countries such as Turkey, they can achieve this goal by acting as positive role models, and by gaining more knowledge on early detection methods (8,9). Therefore, it is imperative that FHP comply with BSE, CBE and MMG testing.…”
mentioning
confidence: 99%